Hope and Resilience During a Pandemic Among Three Cultural Groups in Israel: The Second Wave of Covid-19 - Braun-Lewensohn, Orna; Abu-Kaf, Sarah; Kalagy, Tehila (Frontiers in Psychology, 2021)
The aim of this study was to explore the coping resources of hope (Snyder, 1994) and sense of coherence (Antonovsky, 1987), which are rooted in positive-psychology theory, as potential resilience factors that might reduce the emotional distress experienced by adults from three cultural groups in Israel during the chronic-stress situation of a pandemic. The three cultural groups examined were secular Jews, Ultra-Orthodox Jews, and Arabs. We compared these cultural groups during the second wave of the Covid-19 pandemic, just before the Jewish New Year (mid-September 2020) as a second lockdown was announced. Data were gathered from 248 secular Jews, 243 Ultra-Orthodox Jews, and 203 Arabs, who were 18‒70 years old (M = 37.14, SD = 12.62). The participants filled out self-reported questionnaires including the Brief Symptom Inventory as a measure of emotional/psychological distress (i.e., somatization, depression, and anxiety) and questionnaires about sense of coherence and different types of hope (i.e., intrapersonal, interpersonal, and transpersonal) as measures of coping resources and resiliency. Differences were found between the three groups in terms of several variables. The Arab participants reported the highest levels of emotional distress and the lowest levels of interpersonal and transpersonal hope; whereas the Ultra-Orthodox participants revealed the highest levels of sense of coherence and other resilience factors. A structural equation model revealed that, in addition to the sociodemographic factors, only sense of coherence and intrapersonal hope played significant roles in explaining emotional distress, explaining 60% of the reported distress among secular Jews, 41% among Ultra-Orthodox Jews, and 48% among Arabs. We discuss our findings in light of the salutogenic and hope theories. We will also discuss their relevancy to meaning-seeking and self-transcendence theory in the three cultural groups.